IDDF2018-ABS-0106 Tenofovir alafenamide (taf) compared with tenofovir disoproxil fumarate (tdf) in patients with chronic hbv: week 96 efficacy and safety results in chinese patients enrolled in 2 global phase 3 studies. (8th June 2018) - Chan, Henry Lik-Yuen; Seto, Wai Kay; Fung, Scott; Hou, Jinlin; Pan, Calvin; Chuang, Wan-Long; Chang, Ting-Tsung; Hui, Aric-Josun; Chen, Chi-Yi; Owen Tsang, Tak Yin; Yang, Jenny; Flaherty, John; et al.
Abstract : Background: TAF, a novel prodrug of tenofovir, has demonstrated efficacy noninferior to that of TDF at Week 48 in patients with chronic HBV (CHB) with significantly reduced bone and renal effects. Here we evaluated the efficacy and safety of TAF vs TDF in the subset of patients of Chinese ethnicity enrolled in two overseas studies. Methods: In 2 Phase 3 studies, HBeAg-negative (Study 108) and HBeAg-positive (Study 110) CHB patients were randomised 2:1 to TAF 25 mg QD or TDF 300 mg QD and treated for 96 weeks. In this analysis, the efficacy (HBV DNA). Results: Of 1298 patients randomised and treated, 471 (36%) were of Chinese ethnicity; 156 (TAF 97; TDF 59) and 315 (TAF 207; TDF 108) patients were HBeAg-negative and HBeAg-positive, respectively. For the TAF and TDF groups within each study, baseline characteristics of the study populations were generally similar. Key efficacy results at Weeks 48 and 96 are presented in the Table (table 1). In both HBeAg-negative and HBeAg-positive patients of Chinese ethnicity, the antiviral efficacy of TAF was similar to that of TDF and results were comparable to those in the overall overseas population. Numerically higher percentages of patients treated with TAF achieved normalisation of serum ALT values and anti-HBe seroconversion at Weeks 48 and 96. The safety of TAF and TDF, including changes in renal and bone parameters, were similar to results previously reported in the overall overseas population. Conclusions: In CHB patients of Chinese ethnicity, TAF 25 mg showed similar antiviral efficacy to TDF 300 mg, with less change in bone and renal parameters. Results in this subgroup were comparable to those in the overall population.